2019
DOI: 10.3390/nu11020282
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Dietary Nutrient Ratios in Nutritional Research: Expanding the Concept of Nutrient Ratios to Macronutrients

Abstract: We recently showed that using micronutrient ratios in nutritional research might provide more insights into how diet affects metabolism and health outcomes, based on the notion that nutrients, unlike drugs, are not consumed one at a time and do not target a single metabolic pathway. In this paper, we present a concept of macronutrient ratios, including intra- and inter-macronutrient ratios. Macronutrient intakes from food only, from the What We Eat in America website (summarized National Health and Nutrition E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 35 publications
(55 reference statements)
1
12
0
Order By: Relevance
“…Guidelines for the management of OSO are now available [3,19,59,60,130,131,132]. One of our focus areas over the last five years was on the nutritional aspects related to OSO [3,60,131,132,133,134]. Our intention here is to compile and create preliminary treatment principles for the management of OSO.…”
Section: Nutritional and Physical Activity Considerations For Osomentioning
confidence: 99%
See 1 more Smart Citation
“…Guidelines for the management of OSO are now available [3,19,59,60,130,131,132]. One of our focus areas over the last five years was on the nutritional aspects related to OSO [3,60,131,132,133,134]. Our intention here is to compile and create preliminary treatment principles for the management of OSO.…”
Section: Nutritional and Physical Activity Considerations For Osomentioning
confidence: 99%
“…Insufficiencies in calcium; magnesium; potassium; vitamins B 6 , B 12 , A, D, E and K; and folate, as well as excesses of sodium, phosphorus and most B vitamins (with regard to the Dietary Reference Intakes) may be contributing to OSO [131]. However, a more recent concept of nutrient ratios may better to help explain how the overall nutrient insufficiencies and excesses contribute to OSO and overall health [133,134].…”
Section: Nutritional and Physical Activity Considerations For Osomentioning
confidence: 99%
“…One may argue that the search of ideal elemental ratios is not worthwhile because there is a difference between the dietary ratio and the blood (or serum) ratio, the latter more relevant in health and disease [40]. However, the load of a particular element in a certain foodstuff may well give us an indication of balance/imbalances, without losing the focus on the interactions and bioavailability and as recently referred, the utilization of dietary micronutrient ratios in nutritional studies might well be more informative than focusing on a single nutrient [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…No precise recommendations are existing for the ideal ratio of dietary PUFAs and MUFAs over SFAs. However, based on the recommended unsaturated fatty acids (UFAs: PUFAs + MUFAs) and SFAs daily intakes, MUFAs/SFAs ratio of ∼1, PUFAs/MUFAs ratio of ∼2, and PUFAs + MUFAs/SFAs ratio of 1.6-2 are considered good (13,23). Based on the fatty acid profile ( Table 1), it can be concluded that Korean maize hybrid Ahndaok (No.…”
Section: Maize Hybrids With Desired Fatty Acid Compositionsmentioning
confidence: 99%